Regio- and stereoselectivity in the Paternò-Büchi reaction on furan derivatives - Maurizio D'Auria; Lucia Emanuele; Rocco Racioppi (International Journal of Photoenergy)
The photochemical coupling reaction between 2,3-dihydrofuran and benzaldehyde was studied by using DFT/B3LYP/6−31G+(d,p) method. The regiocontrol of the attack of the benzaldehyde on the double bond is related to the different stabilities of the biradical intermediates. The endo stereoselectivity of the reaction depends on the superposition between HSOMO and LSOMO in the biradical intermediate. In the photochemical reaction between furan and benzaldehyde also the regiocontrol depends on the relative stability of the possible biradical intermediates. The exo stereoselectivity of the coupling reaction depends on the superposition between the HSOMO and LSOMO of the biradical intermediate. The reaction of chiral phenylglyoxylates with furan gave the corresponding adducts with de=15–95%. The stereocontrol can be explained considering the energy gap between the biradical intermediates in the coupling reaction. When the reaction was performed in the presence of zeolite, the diastereoisomeric excess increased. The reaction of benzoin and 2-phenylpropiophenone with furan gave the cycloadduct with high diastereocontrol. All the products were obtained with de>98%. The Paterrnò-Büchi reaction between 2-furylmethanols with aromatic carbonyl compounds also showed high regio- and stereocontrol. On the contrary, when 5-methyl derivatives were used, a lack of regiocontrol was observed. Furthermore, with aliphatic carbonyl compounds, no diastereoselectivity was observed. These results were explained assuming the attack of the excited carbonyl compound on the same side as the hydroxyl group, through the formation of a hydrogen bond or of a complex. This type of attack gave the biradical intermediate in preferential conformations. The relative energies of these conformers account for the observed diastereoselectivity.